2018
DOI: 10.1111/dom.13210
|View full text |Cite
|
Sign up to set email alerts
|

Sustained high‐fat diet modulates inflammation, insulin signalling and cognition in mice and a modified xenin peptide ameliorates neuropathology in a chronic high‐fat model

Abstract: HFD feeding modulates cognitive function, synapse density, inflammation and insulin resistance in the brain. Xenin-25[Lys(13)PAL] ameliorated markers of inflammation and insulin signalling dysregulation and may have therapeutic potential in the treatment of diseases associated with neuroinflammation or perturbed insulin signalling in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 45 publications
5
44
1
Order By: Relevance
“…This was somewhat of a surprise, since the HF diet was ingested the most of all diets before surgery, and that is consistent with other studies [33,34]. Dietary fat causes low-grade gastrointestinal inflammation in rats [35,36] and in humans [37,38], which is diffused by a layer of visceral fat [39]. It may be speculated that loss of visceral fat shortly after surgery may compromise the endotoxemia barrier, which could then underlie higher sickness behavior after surgery in the HF feeding rats [40].…”
Section: Discussionsupporting
confidence: 86%
“…This was somewhat of a surprise, since the HF diet was ingested the most of all diets before surgery, and that is consistent with other studies [33,34]. Dietary fat causes low-grade gastrointestinal inflammation in rats [35,36] and in humans [37,38], which is diffused by a layer of visceral fat [39]. It may be speculated that loss of visceral fat shortly after surgery may compromise the endotoxemia barrier, which could then underlie higher sickness behavior after surgery in the HF feeding rats [40].…”
Section: Discussionsupporting
confidence: 86%
“…Certain studies have found IL-5 to be reduced in diabetes [78], while others have found IL-5 plasma levels to be correlated with glycosylated hemoglobin in diabetic patients [62]. Similarly, increased levels of IL-5 have been shown in HFD-fed mice [90]. We also found IL-12p70 and IL-13 to be closely related to high insulin levels in APP/PS1xdb/db mice, both of which have been shown to be elevated in prediabetic patients [62].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, astrogliosis (elevated levels of GFAP) and microgliosis (elevated levels of Iba1) were not observed in the hippocampus of mice exposed to HFD for 6 months (Lizarbe et al, 2019b). Denver et al (2018) showed astrogliosis and microgliosis in cortex and dentate gyrus of mice fed a HFD for 18 days, but not after 1 month, even though the expression of inflammatory genes such as IKKβ, ERK2, mTOR, NF-kB1, and TLR4 persisted upregulated for 5 months on HFD (Denver et al, 2018). It should be noted, however, that levels of GFAP or Iba1 alone might not report on changes in cellular morphology, and such simplistic assessments might contribute to reported controversies (Gzielo et al, 2017).…”
Section: Inflammation and Gliosismentioning
confidence: 95%